2018
DOI: 10.1186/s12864-018-5054-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of circular RNAs between soybean cytoplasmic male-sterile line NJCMS1A and its maintainer NJCMS1B by high-throughput sequencing

Abstract: BackgroundCytoplasmic male sterility (CMS) is a natural phenomenon of pollen abortion caused by the interaction between cytoplasmic genes and nuclear genes. CMS is a simple and effective pollination control system, and plays an important role in crop heterosis utilization. Circular RNAs (circRNAs) are a vital type of non-coding RNAs, which play crucial roles in microRNAs (miRNAs) function and post-transcription control. To explore the expression profile and possible functions of circRNAs in the soybean CMS lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…Recently, several differentially expressed (DE) circRNAs that are involved in programmed cell death (PCD) and might play an important role in CMS have been found among the soybean CMS line NJCMS1A, and its maintainer NJCMS1B. It indicates that circRNAs may play a role in regulating flower and pollen development, and provide novel insights into the mechanisms of CMS [18]. However, the circRNA–miRNA–mRNA network was not established in the abovementioned study, and the clear interactions of circRNAs, miRNAs, and mRNAs among male reproductive development need further study.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several differentially expressed (DE) circRNAs that are involved in programmed cell death (PCD) and might play an important role in CMS have been found among the soybean CMS line NJCMS1A, and its maintainer NJCMS1B. It indicates that circRNAs may play a role in regulating flower and pollen development, and provide novel insights into the mechanisms of CMS [18]. However, the circRNA–miRNA–mRNA network was not established in the abovementioned study, and the clear interactions of circRNAs, miRNAs, and mRNAs among male reproductive development need further study.…”
Section: Introductionmentioning
confidence: 99%
“…Considering circular structures and relatively low expression levels of circRNAs, an additional protocol that using linear RNase R for library preparation has become the preferred method for greatly enriching circRNAs. This method has been widely used in plant circRNA studies and yielded high confidence circRNAs in maize, soybean, bamboo, tomato, and grape (Zuo et al, 2016;Chen L. F. et al, 2018;Gao et al, 2019;Luo et al, 2019;.…”
Section: Biogenesis and Discovering Of Plant Circrnasmentioning
confidence: 99%
“…Besides this, circular RNAs (circRNAs) are crucial non‐coding RNAs, which play imperative roles in miRNAs function and post‐transcription control. Chen et al () found that 83 miRNAs were predicted from the differentially expressed circRNAs, some of which were strongly related to pollen development and male fertility in soybean. Further, 165 new circRNAs were reported and it was predicted that they at least contain one internal ribosome entry site element and an open reading frame, indicating their potential to encode polypeptides or proteins, it is assumed that there may be some relation to MS in soybean.…”
Section: Molecular Mechanisms Of Male Sterility In Soybeanmentioning
confidence: 99%
“…Besides this, circular RNAs (circRNAs) are crucial non-coding RNAs, which play imperative roles in miRNAs function and post-transcription control. Chen et al (2018) found that 83 miR-NAs were predicted from the differentially expressed circRNAs, some of which were strongly related to pollen development and It is widely accepted that CMS in the plant is closely related to mitochondrial genome rearrangement, and many trait-determining mitochondrial genes could be suppressed or activated by Rf-genes (Bentolila & Stefanov, 2012;Chen et al, 2017;Zheng et al, 2012). In fact, some specific CMS-related genes have been identified as direct or indirect MS due to damage or abnormalities in the mitochondrial genome (Kazama et al, 2019).…”
Section: Molecul Ar Mechanis Ms Of Male S Terilit Y In Soyb E Anmentioning
confidence: 99%